2004
DOI: 10.1111/j.1468-3083.2004.01046.x
|View full text |Cite
|
Sign up to set email alerts
|

Sun awareness in Maltese secondary school students

Abstract: Attitude change lags behind knowledge. Future school sun awareness interventions need to take into account gender and age differences in students' attitudes and perspectives. They should aim at motivating attitude change and preventive behaviour through consistent and repeated sun-education messages that are supported by a sun-conscious school environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
27
2
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 23 publications
(31 reference statements)
4
27
2
2
Order By: Relevance
“…Notably, lower percentages of sun protection measures were reported by Saridi et al whose study revealed that only 50% of the participants were using hats and stayed in the shade; the use of hat and sunglasses indicated 39% and 25.5% of the study participants, respectively (Saridi, 2009). A number of studies reported that less than 11.5% of respondents indicated that they always use sunglasses, sunscreen, protective clothes and hat against sun exposure (Lowe et al, 2000;Livingstonet al, 2001;Aquilina et al, 2004;Stankeviciute et al, 2004). Ergin et al found that the most of the study participants generally avoided the harmful effects of the sun by staying in the shade (Ergin, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, lower percentages of sun protection measures were reported by Saridi et al whose study revealed that only 50% of the participants were using hats and stayed in the shade; the use of hat and sunglasses indicated 39% and 25.5% of the study participants, respectively (Saridi, 2009). A number of studies reported that less than 11.5% of respondents indicated that they always use sunglasses, sunscreen, protective clothes and hat against sun exposure (Lowe et al, 2000;Livingstonet al, 2001;Aquilina et al, 2004;Stankeviciute et al, 2004). Ergin et al found that the most of the study participants generally avoided the harmful effects of the sun by staying in the shade (Ergin, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The main objectives of these studies were; obtaining locally relevant information about primary and secondary prevention, identifying populations at high risk, and evaluating the running educational programs (Aquilina, Gauci, Ellul, & Scerri, 2004;Cokkinides et al, 2006;Geller et al, 2005;Harrison, Saunders, & Nowak, 2007;Jones, Oh, Corkery, Hanley, & Egan, 2007). Unfortunately, skin cancer publications in the KSA are scarce which represents challenge for the current work.…”
mentioning
confidence: 99%
“…S'agissant enfin du risque cancérigène associé au soleil, il est connu par tous ou presque, mais des croyances erronées persistent, comme l'idée que l'exposition au soleil des enfants est « bonne pour la santé » [20]. Les usages sociaux du soleil et les conceptions du corps qui s'y rapportent constituent des obstacles redoutables pour la prévention, comme l'a montré une abondante littérature [21][22][23][24][25]. Ils pourraient à ce titre être ciblés par la prévention.…”
Section: Discussionunclassified